Development of Electrochemical Aptasensor for Lung Cancer Diagnostics in Human Blood; Sensors; Vol. 21, iss. 23 - Shabalina A. Anastasiia; Sharko D. Darya; Glazyrin Yu. Yury; Bolshevich E. Elena; Dubinina O. V. Oksana Valerievna; Kim A. Anastasiia; Veprintsev D. Dmitry; Lapin I. Ivan; Zamay G. Galina; Krat A. Alexey; Zamay S. Sergey; Svetlichnyi V. Valery; et al. (2021, 2021)
Title screen